Characterization of hot pressed CuAl–TiC composites with different TiC grain sizes - Islak, Serkan; Çelik, Ertuğrul; Kır, Durmuş; Özorak, Cihan (Allerton Press, 2016)
In this study, the CuAl–TiC composite materials were produced using hot pressing process. Effect of TiC grain size (0.2, 4 and 20 μm) on some properties of these materials was investigated experimentally. Production of CuAl–TiC composites was carried out under pressure of 35 MPa, at 700°C, and for a sintering time of 5 minutes. SEM-MAP studies showed that the TiC grains were relatively homogeneously distributed in the CuAl matrix. Microstructure analysis revealed that the composite materials consist of Cu, Al, Cu9Al4, CuAl2 and TiC phases. With the decreasing of TiC grain size, the hardness, transverse rupture strength, relative density and sintered density of composites increased.
Keywords: Sintering; Hardness; TRS; Grain Size; CuAl–TiC Composites; Microstructure; 8. Economic growth; 16. Peace & justice